'As many options as there are, there are just not enough for me': Contraceptive use and barriers to access among Australian women. (October 2014) - Dixon, Suzanne C.; Herbert, Danielle L.; Loxton, Deborah; Lucke, Jayne C.
Abstract: Objective A comprehensive life course perspective of women's experiences in obtaining and using contraception in Australia is lacking. This paper explores free-text comments about contraception provided by women born between 1973 and 1978 who participated in the Australian Longitudinal Study on Women's Health (ALSWH). Methods The ALSWH is a national population-based cohort study involving over 40, 000 women from three age groups, who are surveyed every three years. An initial search identified 1600 comments from 690 women across five surveys from 1996 (when they were aged 18–23 years) to 2009 (31–36 years). The analysis included 305 comments from 289 participants. Factors relating to experiences of barriers to access and optimal contraceptive use were identified and explored using thematic analysis. Results Five themes recurred across the five surveys as women aged: (i) side effects affecting physical and mental health; (ii) lack of information about contraception; (iii) negative experiences with health services; (iv) contraceptive failure; and (v) difficulty with accessing contraception. Conclusion Side effects of hormonal contraception and concerns about contraceptive failure influence women's mental and physical health. Many barriers to effective contraception persist throughout women's reproductive lives. Further research is needed into reducing barriers and minimising negative experiences, to ensure optimal contraceptive access for Australian women. Chinese Abstract 摘 要目的 从一种全面的生命历程的角度来看，澳大利亚妇女缺乏获取和采用避孕方法方面的经验。本文探究了1973年至1978年间出生，参加澳大利亚妇女健康纵向研究（ALSWH）的女性所提供的关于避孕的自由评论。 方法 ALSWH是一项国家性的以人群为基础的群组研究项目，有来自各个年龄组的40, 000多名女性参加，每三年对她们进行一次调查。最初搜索到的是在1996年（当时她们18-23岁）至2009年（当时她们31-36岁）参与五项研究的690名女性所做的1600条评论。本项分析包括289名参与者的305条评论。采用主题分析方法确定并探究了与所面临的障碍和采用理想避孕方法等方面的经验相关的因素。 结果 随着这些女性年龄的增长，五项研究的五个主题再次出现：（i）影响生理和心理健康的副作用；（ii）缺乏避孕相关的信息；（iii）卫生服务的负面经历；（iv）避孕失败；（V）成功避孕的困难。 结论 激素避孕和对担心避孕失败的副作用影响女性的生理和心理健康。许多有效避孕的障碍会始终贯穿女性的育龄期。下一步的研究应减少障碍并使负面的经历最小化，为澳大利亚妇女确保最佳的避孕方法。